The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1080/00952990802455469
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Medicine in the Treatment of Drug Addiction

Abstract: Traditional herbal treatments can compliment pharmacotherapies for drug withdrawal and possibly relapse prevention with less expense and perhaps fewer side effects with notable exceptions. Both acupuncture and herbal treatments need testing as adjuncts to reduce doses and durations of standard pharmacotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 114 publications
(93 reference statements)
0
67
0
1
Order By: Relevance
“…Today peyote is used sacramentally by groups including the Native American Church (NAC) (Stewart, 1987) and the Huichol of northern Mexico (Meyerhoff, 1974). It has often been stated that taking peyote in the context of NAC ceremonies helps alcoholics achieve and maintain sobriety (Albaugh and Anderson, 1974b;Garrity, 2000;Kunitz and Levy, 1994;Lu et al, 2009). Proposed psychological mechanism includes emotional catharsis (Albaugh and Anderson, 1974a) and improved self-understanding and motivation for sobriety (Garrity, 2000).…”
Section: Peyotementioning
confidence: 97%
See 1 more Smart Citation
“…Today peyote is used sacramentally by groups including the Native American Church (NAC) (Stewart, 1987) and the Huichol of northern Mexico (Meyerhoff, 1974). It has often been stated that taking peyote in the context of NAC ceremonies helps alcoholics achieve and maintain sobriety (Albaugh and Anderson, 1974b;Garrity, 2000;Kunitz and Levy, 1994;Lu et al, 2009). Proposed psychological mechanism includes emotional catharsis (Albaugh and Anderson, 1974a) and improved self-understanding and motivation for sobriety (Garrity, 2000).…”
Section: Peyotementioning
confidence: 97%
“…Early-stage clinical trials of psilocybin for nicotine dependence (Johnson et al, 2014) and alcohol dependence (Bogenschutz et al, 2015) have recently been completed, and further trials are currently under way. Observational studies have suggested that sacramental use of plant materials containing classic hallucinogens (peyote, containing mescaline, or ayahuasca, containing DMT) suggests that these practices are associated with decreased disordered use of substances and few if any detrimental effects (Albaugh and Anderson, 1974b;Barbosa et al, 2012;Doering-Silveira et al, 2005;Fabregas et al, 2010;Garrity, 2000;Halpern et al, 2005;Halpern et al, 2008;Kunitz and Levy, 1994;Lu et al, 2009;Roy, 1973). Ayahuasca and ibogaine are being used to treat addictions in many retreat centers and treatment programs in Latin America and the Caribbean, but efficacy studies have not been done.…”
Section: Historical Backgroundmentioning
confidence: 97%
“…Several studies have highlighted the efficacies of medicinal herbs for reduction of ethanol, nicotine, and opioid dependence (Gupta and Rana 2008;Lu et al 2009). In particular, some preclinical studies have reported that Hypericum perforatum L., Withania somnifera Dunal, Valeriana officinalis L., and Passiflora incarnata L. have potential in the treatment of morphine withdrawal, due to their antidepressant and anxiolytic properties (Dhawan 2003;Feily and Abbasi 2009;Kasture et al 2009;Sharifzadeh et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, others have narrowed their search to specific populations of interest such as Native Hawaiians [20], Hispanic adolescents [21], African Americans [22], or Australian Aboriginals [23-26]. A few reviews have focused on interventions to treat Indigenous people, but these cited interventions are not holistically or culturally-based [27,28]. One literature review considered evidence-based practice in Native American mental health service delivery, but deliberately excluded treatments that targeted substance use [29].…”
Section: Introductionmentioning
confidence: 99%